Influence of Extraction Variables on the Structure and Physical Properties of Salmon Gelatin - (:unkn) unknown (ELSEVIER SCI LTD, 2017)
This work focuses on investigating the effect of extraction conditions (pH and time) on the biochemical and physical properties of salmon gelatin (SG). SG was extracted from salmon skins under different pH and time conditions at 60 degrees C. The characterization of the material considered proximate composition, amino acid profile, molecular weight (MW), gel strength, X-Ray diffraction, thermal properties, dynamic mechanical properties and dynamic vapour sorption analysis. Results showed that higher protein content was obtained with extraction condition pH5/2h, while lower protein content was obtained at condition pH3/5h. Extraction performed at pH5 produced SG with MW > 120 kDa, while processing condition at pH3 resulted in MW bands distributed between 20 and 100 kDa. Higher contents of proline and hydroxyproline were detected in SG with high MW. This behaviour was directly correlated with gel strength and thermo-mechanical properties: higher gel strength and E modulus were observed in SG with high MW, suggesting higher amount of triple helical structures in gelatin matrix. This was also supported by higher values of tans detected as the MW of SG decreased. This may be related with decreasing the crystalline fraction of SG. Thermal properties revealed no significant differences in melting temperature and glass transition temperature values among samples. The melting energy was significantly lower for SG with lower MW. This was confirmed by X-Ray diffraction where the intensity of the diffraction peak at similar to 2 theta = 8 degrees significantly decreased for SG extracted under more aggressive conditions. Finally, gelatin extracted under mild conditions showed higher moisture content, which was in agreement with higher amounts of triple-helix structures. Our results suggest the possibility to modulate the physical properties of SG by tuning the extraction process to obtain tailored gelatin structures for high-value applications in food technology, tissue engineering and biomedicine. (C) 2017 Elsevier Ltd. All rights reserved.